The Institutional Ownership and Firm Performance: Evidence from The Capital Bank - Bhenu Artha; Bahri Bahri; Niken Permata Sari; Utami Tunjung Sari; Ulfa Rani Manurung (Profesional Muda Cendekia Publishing, 2021)
Governments have increasingly liberalized their policies in recent years to attract foreign investment, as they have witnessed a favorable impact – both direct and indirect – on target country firms and economic development. The effect of multiple large shareholders on firm performance cannot be considered in isolation, however, as the institutional and developmental conditions vary across countries. The objective of this research is to determine the influence of institutional ownership to firm performance especially in The Capital Bank. This research uses quantitative methods and linear regression analysis. The results of the analysis show that there is no effect of institutional ownership on ROA and ROE at The Capital Bank for the period December 2012 – December 2019. There is no effect of institutional ownership on the performance of The Capital Bank because the percentage of institutional ownership less than 50% so the contribution does not have much effect on the company's strategic decisions.